Cardiorespiratory Fitness Measured with Cardiopulmonary Exercise Testing and Mortality in Patients with Cardiovascular Disease: A Systematic Review and Meta-Analysis - Garcia-Hermoso, A (Elsevier B.V., 2021)
Background: Cardiorespiratory fitness (CRF) is inversely associated with mortality in apparently healthy subjects and in some clinical populations, but evidence for the association between CRF and all-cause and/or cardiovascular disease (CVD) mortality in patients with established CVD is lacking. This study aimed to quantify this association. Methods: We searched for prospective cohort studies that measured CRF with cardiopulmonary exercise testing in patients with CVD and that examined all-cause and CVD mortality with at least 6 months of follow-up. Pooled hazard ratios (HRs) were calculated using random-effect inverse-variance analyses. Results: Data were obtained from 21 studies and included 159,352 patients diagnosed with CVD (38.1% female). Pooled HRs for all-cause and CVD mortality comparing the highest vs. lowest category of CRF were 0.42 (95% confidence interval (95%CI): 0.28–0.61) and 0.27 (95%CI: 0.16–0.48), respectively. Pooled HRs per 1 metabolic equivalent (1-MET) increment were significant for all-cause mortality (HR = 0.81; 95%CI: 0.74–0.88) but not for CVD mortality (HR = 0.75; 95%CI: 0.48–1.18). Coronary artery disease patients with high CRF had a lower risk of all-cause mortality (HR = 0.32; 95%CI: 0.26–0.41) than did their unfit counterparts. Each 1-MET increase was associated with lower all-cause mortality risk among coronary artery disease patients (HR = 0.83; 95%CI: 0.76–0.91) but not lower among those with heart failure (HR = 0.69; 95%CI: 0.36–1.32). Conclusion: A better CRF was associated with lower risk of all-cause mortality and CVD. This study supports the use of CRF as a powerful predictor of mortality in this population. © 2021